Uji Aktivitas Penyembuhan Luka Nanoemulsi Ekstrak Etanol 96% Daun Sablo (Acalypha Wilkesiana) pada Tikus Wistar - Erika Vira Buana Putri (Fakultas Farmasi, 2025)
Wound is tissue damage that requires proper treatment to prevent complications. The leaves of Acalypha wilkesiana are known to contain flavonoid compounds such as luteolin with anti-inflammatory and antioxidant properties support wound healing process. Nanoemulsion needed to increasing stability, and bioavailability of active compounds. This study aims to evaluate the wound healing activity of 10% nanoemulsion formulated from 96% ethanol extract of Acalypha wilkesiana leaves in male Wistar rats. A total of 24 rats were divided into four groups: negative control, positive control, extract treatment, and nanoemulsion treatment. The parameters observed include wound condition, epithelialization time, percentage of wound closure measured on days 0, 3, 7, and 15. The nanoemulsion group showed had the highest percentage of wound closure (92.81%) and the fastest epithelialization time (day 8). Statistical analysis using One-Way ANOVA and Post Hoc Tukey test showed significant differences (p < 0.05) between the treatment groups, indicate that the nanoemulsion formulation was more effective in accelerating the wound healing process and holds potential as topical therapy for mild to moderate wounds compared to the other groups.
Reupload Repository hasyim Mei 2026 :: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: Acalypha wilkesiana leaves; wound healing; nanoemulsion